If y = 5/2(e^(x/5) + e^(-x/5)), prove that y'' = y/25.

If y = 5/2(e^(x/5) + e^(-x/5)), prove that y'' = y/25.

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

I expanded the bracket:
y = 5/2(e^(x/5)) + 5/2(e^(-x/5))

Then I took the first derivative:

y ' = 5x/10(e^(x/5)) - 5x/10(e^(-x/5))

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.